Study on the comet assay and micronucleus test in eudrilus eugeniae earthworms’ coelomocytes exposed with tannery industrial effluents - R, Mathivanan; R, Chandirasekar (Kongunadu Research Journal, 2020)
Tannery effluents having the different kind’s chemical compounds are extensively used to the production of leather industries and it’s considered as rich potential of environmental pollutant.Earthworms are easily affecting the toxic chemical in environmentally and in this organism is good experimental animal for monitoring the soil pollution and terrestrial ecosystem. In this study, we taken from the industrial raw tannery effluents and the experimental animal in earthworm species of Eudrilus eugeniae (10 for each group) were introduced to 48 hrs for tannery effluent in five different concentrations like 10 ml, 20ml, 30ml, 40 ml, and 50 ml and to find out LC50 level. The LC50 was found at 35 ml concentration. The study was used to the LC50/2, LC50, 2XLC50 for 48 hrs. Then the genotoxicity level was evaluated in Eudrilus eugeniae species. After that we collect earthworm’s coelomocytes by using the micronucleus (MN) test and comet assay (CA) test. Result of the study, MN and CA level was significantly increased in both genotoxicity and cytotoxicity assays and the high concentration of effluent to promote the increased level of DNA damage and micronucleus in Eudrilus eugenie species.